2005
DOI: 10.1079/wps200447
|View full text |Cite
|
Sign up to set email alerts
|

Ascites and venous carbon dioxide tensions in juvenile chickens of highly selected genotypes and native strains

Abstract: A previous study by this group demonstrated that a high carbon dioxide tension in venous blood (pvCO 2 ) of juvenile broiler chickens is a reliable predictor for ascites susceptibility. In a new experiment with five highly selected genetic stocks and two ascites resistant old breeds we studied levels and variability of pvCO 2 within each stock at an early age. Effects of different selection traits (principally growth rate) between fast growing sire lines and slower growing dam lines and a commercial hybrid on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 40 publications
5
21
3
Order By: Relevance
“…Mild hypoxia was found to elicit an increase in heart rate [169,170], which suggests that the AS-S birds in that study experienced O2 shortage already at the time of hatch, even when kept under optimal conditions. A higher mean partial pressure of CO2 in broilers' venous blood (a marker for lung ventilation rate) on d 11 was found to be associated with increased ascites susceptibility [171,172]. Those results indicate that ASsusceptible birds suffer O2 shortage at an early age.…”
Section: The Heartsupporting
confidence: 50%
“…Mild hypoxia was found to elicit an increase in heart rate [169,170], which suggests that the AS-S birds in that study experienced O2 shortage already at the time of hatch, even when kept under optimal conditions. A higher mean partial pressure of CO2 in broilers' venous blood (a marker for lung ventilation rate) on d 11 was found to be associated with increased ascites susceptibility [171,172]. Those results indicate that ASsusceptible birds suffer O2 shortage at an early age.…”
Section: The Heartsupporting
confidence: 50%
“…Insufficient thyroid hormone activity to regulate metabolism, related to genetic background, will therefore become especially apparent at low ambient temperature (Scheele et al, 1992). Recent results (Buys et al, 1999;Decuypere et al, 2000;Scheele et al, 1992Scheele et al, , 2005Luger et al, 2001;Hassanzadeh et al, 2010) confirmed those of the Scheele et al (1992) and indicated that hypothyroidism, observed in lines combining a favourable FCR and fast growth, plays an important part in the reduction of oxygen consumption that lead to anoxia, heart failure and ascites.…”
Section: A Interaction Between Endogenous and Exogenous Factorssupporting
confidence: 49%
“…Although ascites is conventionally associated with the rapid growth rate of broilers, high metabolic rates and high oxygen requirements (Hassanzadeh, 1997;Hassanzadeh et al, 1997a, b, Julian, 1993, 2005Balog, 2003), recent data indicated that ascites is not always caused by an increased oxygen requirement of fast growth rate per se at low altitude, but by an impaired oxygen supply to sustain the fast growth rate Scheele et al, 2005;Malan et al, 2003;Hassanzadeh et al, 2010). mentioned that thyroid function is an important regulatory mechanism of the metabolic rate, it is plausible that early selection for feed conversion (FCR) could have resulted in functional of hypothyroidism, as ascites sensitive birds are believed to be limited in their thyroxin (T 4 ) production (Scheele et al, 1992;Scheele, 1996).…”
Section: A Interaction Between Endogenous and Exogenous Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, during the growing period at low altitude, the highest blood glucose level was found in the HA-OX group at 7 and 21 days old and the lowest plasma T 3 and T 4 levels and highest PCV values were found in the LA-NOX group at 42 days old. However, some researchers have suggested that there is not always an association between ascites syndrome and the haematocrit values (Shlosberg et al, 1998;Hassanzadeh et al, 2000;Scheele et al, 2005). As reported by Zhang et al (2007), significant increase in the haematocrit and Hb values were obtained in the birds reared at high altitude compared with those birds reared at low altitude.…”
Section: Discussionsupporting
confidence: 57%